Finding The Data Hyponym and An Analysis of Novel “The Wild Robot by Peter Brown” - Anabella Tiara Zilullah; Hilma Safitri; Barbie Amoura Keyra; Dina Syaripatul Hikmawati; Galuh Septina Candra; Salwa Asy Syifa Dema; Sandy Anggriawan Wiharjo (INDO PUBLISHING, 2025)
This study examines the semantic relationships of hyponyms in Peter Brown's novel, The Wild Robot, focusing on how specific word choices contribute to meaning and categorization within the narrative. With a qualitative approach and based on the theories of Cruse (1986) and Lyons (1995), 20 hyponymic expressions were found in the novel. These expressions were then grouped into semantic fields, including animals, plants, technology, and residences. For example, the words